The influence of Indonesian micro productive assistance policy on MSME resilience / Sekar Maulidia Hapsari, Mardhiyah Hayati and Diah Mukminatul Hasyimi - Hapsari, Sekar Maulidia; Hayati, Mardhiyah; Hasyimi, Diah Mukminatul (Universiti Teknologi Mara Selangor, 2023)
The pandemic has had a big impact on MSME actors so they cannot carry out their usual activities. One of the projects in economic recovery is the Banpres for Small and Medium Enterprises (BPUM). The research method used is a quantitative research approach using data collection methods, namely questionnaires, documentation and literature study. The sample in this study is the community receiving BPUM funds in Kec. Sukarame Bandar Lampung. Overall, the results of the study show that the results of a simple linear regression using a partial test (T test) on the BPUM (X) policy have a positive and significant effect on MSME resilience. So it can be concluded that the BPUM policy affects the resilience of MSMEs in Sukarame District, Bandar Lampung City.